Improving Public Speaking Skills through YouTube Media for Sixth Grade Students of SDN 2 Daleman, Education Subdivision Coordinator of Tulung District, Klaten Regency, Academic Year 2024/2025 - Syamsiyah, Siti; Basuki, Basuki; Putut Setiyadi, Dwi Bambang; Hersulastuti, Hersulastuti; Herawati, Nanik (Society : Jurnal Pengabdian Masyarakat, 2025)
This study aims to improve the public speaking skills of sixth-grade students at SDN 2 Daleman through the utilization of YouTube as an audiovisual-based learning medium. Public speaking is a crucial component of oral communication competence that needs to be developed from an early age, as it influences students’ confidence, critical thinking, and ability to express ideas in public. Initial observations indicated that most students faced difficulties in structuring their speeches systematically, using proper pronunciation and intonation, and showing appropriate expression and vocal control during presentations.The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each comprising planning, action, observation, and reflection stages. The subjects were 17 sixth-grade students, consisting of 8 boys and 9 girls. Data were collected through observation, documentation, interviews, and speech performance tests. The success indicators were determined by the increase in the number of students who met the Minimum Mastery Criteria (MMC) of 75 and improvements in specific aspects of public speaking, including expression, pronunciation, intonation, voice volume, and content structure.The results showed a significant improvement in students’ public speaking skills through the use of YouTube media. In the pre-cycle stage, only 7 out of 17 students (41%) achieved the MMC. After the first cycle of implementation, the number increased to 10 students (58%). By the second cycle, 15 students (88%) met or exceeded the target. In addition to the quantitative improvement, qualitative enhancements were observed in students’ delivery of speech elements.Learning improvement was also evident across multiple performance aspects, such as clarity of pronunciation, appropriate expression, dynamic intonation, mastery of content, and proper vocal projection. The effective use of YouTube, particularly through a modeling approach featuring high-achieving students as role models, proved to be a powerful motivator and conceptual clarifier. Moreover, it enabled students to engage in self-reflection by watching their own recorded speeches. Therefore, YouTube serves not only as a visual aid but also as a strategic tool to enhance oral communication skills in the context of 21st-century learning.